Analisis nilai karakter cerita legenda dalam buku siswa kelas iv sd tema 8 “daerah tempat tinggalku” kurikulum 2013 - Wiji Istari; Retno Winarni; Anesa Surya (Didaktika Dwija Indria, 2021)
This research was conducted for describing the value of the character in the legend story in the fourth grade students book theme 8 "Daerah Tempat Tinggalku" curriculum 2013. The research design in this study used a qualitative descriptive approach. The method that used is content analysis. The data used are words, sentences and paragraphs in the legend story. Sources of data in this research were books for fourth grade Elementary students at theme 8 "Daerah Tempat Tinggalku". The sampling technique was purposive sampling. Data collection techniques used documentation techniques. Test the validity of the data in this research used semantic validity and reliability validity. The data analysis technique used the Hermeneutic approach. The results showed that (1) honest character values were found 2 citation character values. (2) the value of the character of responsibility found 2 quotes of character values. (3) there are 2 quotations for intelligent character values. (4) clean and healthy character values are not found in the 5 legend stories. (5) the caring character value is found 12 character value quotes. (6) the value of creative character was found 2 quotes of character values. (7) the value of mutual cooperation character found 1 quote character value. Keywords: Character Value, Legend Stories, Student Book, Elementary School